Architectural Attributes of Apartment Houses Built in Pristina from 2000 until 2021 (Prostor, 2024)
This study analysed the architectural attributes of apartment houses built in Pristina from 2000 until 2021. The case studies were analysed through - the urban, the building and the apartment criteria. By comparing them with spatial standards of POS regulations, the architectural attributes of apartment houses in Pristina were assessed and recommendations for the enhancement of the design quality were set.